Politik Hukum Pembentukan Peradilan Tata Usaha Militer Dalam Perspektif Negara Hukum - Zulkarnain, Akbar; Deliana, Evi; Zulwisman, Zulwisman (Jurnal Ilmiah Wahana Pendidikan, 2025)
The military is a member of the armed forces of a country that is regulated based on the provisions of laws and regulations. The establishment of the Military Administrative Court is intended as one of the judicial institutions within the scope of military justice that examines, decides, and resolves disputes over the Administration of the Armed Forces. This type of research can be classified into the type of Normative Dogmatic research which is the main problem, namely the establishment of military administrative courts. This research uses primary and secondary data sources. With data collection techniques, it is arranged by grouping books, journals, laws and regulations. The Military Administrative Court, which has the authority to resolve military administrative disputes, is regulated in Law No. 31 of 1997 concerning Military Courts, which is a legal vacuum due to the absence of procedural law that regulates it. This research describes how the politics of law and the ideal conception of the Military Administrative Court in Indonesia.